A Computational Insight on the Effect of Encapsulation and Li Functionalization on Si12C12 Heterofullerene for H2 Adsorption: A Strategy for Effective Hydrogen Storage - Jaiswal, Ankita; Chakraborty, Brahmananda; Sahu, Sridhar (ACS applied energy materials, 2023)
This article presents the hydrogen storage capacity of Ar encapsulated and Li functionalized Si12C12 heterofullerene using state-of-the-art Density Functional Theory (DFT) simulations. We find that the Li atom regioselectively prefers to bind at the top of the tetragonal sites of Ar encapsulated Si12C12 heterofullerene with a maximum binding energy of 2.02 eV. Our study reveals that inert gas Ar encapsulation inside bare Si12C12 provides greater stability to the heterofullerene by reducing the distortion. Hence, it provides a steady platform for Li decoration and successive H2 adsorption. The adsorption energies of sequentially hydrogen-adsorbed Si12C12Li6, Ne@Si12C12Li6, and Ar@Si12C12Li6 are compared, and it is observed that H2 molecules prefer to adsorb over Li decorated Ar@Si12C12 with maximum adsorption energy. Each Li atom decorated over Ar@Si12C12 adsorbs a maximum of 5 H2 molecules with an optimum adsorption energy of 0.11–0.22 eV, resulting in a gravimetric density of 9.7 wt % which is well above the US-DoE target. The adsorption mechanism of H2 molecules over Ar@Si12C12Li6 has been thoroughly investigated using the electrostatic map and topological analyses. The type of interaction involved in the adsorption of H2 molecules over the Ar@Si12C12Li6 surface is found to be a weak noncovalent interaction. Thermodynamic study reveals that almost all the 30 H2 molecules remain adsorbed over the system at a low temperature of 100–120 K and undergo maximum desorption at 250–400 K, maintaining the structural integrity, which infers that the Ar@Si12C12Li6 nanocage can be considered as a potential hydrogen storage material.